2016
DOI: 10.1080/14697688.2016.1260759
|View full text |Cite
|
Sign up to set email alerts
|

The role of volume in order book dynamics: a multivariate Hawkes process analysis

Abstract: We show that multivariate Hawkes processes coupled with the nonparametric estimation procedure first proposed in can be successfully used to study complex interactions between the time of arrival of orders and their size, observed in a limit order book market. We apply this methodology to high-frequency order book data of futures traded at EUREX. Specifically, we demonstrate how this approach is amenable not only to analyze interplay between different order types (market orders, limit orders, cancellations) b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 45 publications
6
48
1
Order By: Relevance
“…This suggests that most inhibition effects are short lived and the effect of an event arrival is towards an increase of the overall intensity. This is in line with what was found in and Rambaldi et al (2016), where the inhibitions effects were shown to be mostly concentrated around the typical market reaction time.…”
Section: 33supporting
confidence: 92%
See 2 more Smart Citations
“…This suggests that most inhibition effects are short lived and the effect of an event arrival is towards an increase of the overall intensity. This is in line with what was found in and Rambaldi et al (2016), where the inhibitions effects were shown to be mostly concentrated around the typical market reaction time.…”
Section: 33supporting
confidence: 92%
“…For all events T a , L a and C a the most visible feature is the strong self-exciting interaction. This has been confirmed in several works , Rambaldi et al (2016)) and can be traced to order-splitting strategies and herding behaviors. Signatures of typical trading patterns can be seen also in the kernels L a → C a , L a → C b , where the positive value of the kernel arises form agents canceling and replacing their limit orders with or without switching sides.…”
Section: Analysis Of the G Matrix: Unveiling Mutual Interactions Betwsupporting
confidence: 62%
See 1 more Smart Citation
“…In the work of [Huang et al, 2015], and many other related works, the order size is supposed to be constant. It is however clear from empirical analyses that the order sizes have remarkable statistical properties, and that such information is relevant to the LOB dynamics, see for instance [Abergel et al, 2016][Muni Toke, 2015 [Rambaldi et al, 2017].…”
Section: Figure 2: Queue Reactive Model Order Intensitiesmentioning
confidence: 99%
“…To name a few, Bacry and Muzy (2014), Bacry et al (2013Bacry et al ( , 2016 propose various models of price and order flow models, whereas Bacry et al (2015) is an extensive survey of the application of Hawkes process in finance. In the specific context of limit order books, Large (2007) is an early study of Hawkes processes applied to order book modelling, Hawkes-process-based limit order book models are introduced and mathematically investigated in Abergel and Jedidi (2015), Zheng et al (2014) and, in a sligthly different direction, Rambaldi et al (2016) models the order volumes -in addition to their types -based on a multivariate Hawkes process.…”
Section: Introductionmentioning
confidence: 99%